Requirements for surface plasmon resonance excitation in air with slightly tilted fiber Bragg gratings - González-Vila, Álvaro; Loyez, Médéric; Ioannou, Andreas; Caucheteur, Christophe (My University, 2018)
Surface plasmon resonance (SPR) excitation has been widely studied in the well-known Kretschmann prism configuration, leading to a large variety of refractometric optical sensors. In recent research, this bulky optical device has found a counterpart thanks to the use of metal-coated optical fibers, mainly allowing to considerably reduce the size of the sensors. Some approaches make use of multimode, etched or unclad fibers while the grating-based alternatives are mostly focused on uniform, long period or tilted fiber Bragg gratings (TFBGs). However, plasmonic optical fiber sensing has been pretty much restricted to aqueous solutions due to the remarkable applications of these devices in (bio)chemical sensing. This work gives the roadmap through SPR excitation in air by using a 10° TFBG refractometer. With regard to aforementioned developments, the photo-inscription process is carried out with an excimer laser emitting at 193 nm, which creates the grating planes in a position close to the core-cladding interface. By doing so, it is possible to obtain a cladding mode resonance comb covering the range of the spectrum that corresponds to refractive index values around the one of the air, without the need of using highly tilted FBGs. Indeed, the coupling of cladding modes to the outer medium can be observed in the optical transmitted spectrum of a bare TFBG. In addition, the thickness of the gold thin-film deposited at the grating location is reduced to one third of the one used for SPR excitation in liquids. In this way, all the cladding modes are reflected by the metal when the TFBG is immersed in solution but when it is left in the air a SPR signature appears in the spectrum. The methods described in the present paper are intended to support further developments on plasmonic optical fiber solutions applied to refractive index sensing in gaseous atmospheres.
Keywords: Fiber Bragg gratings; Gas sensor; Optical fiber sensor; Plasmonics; Refractive index; Sensor; Surface plasmons; Tilted fiber Bragg grating